SnO2, ZnO and related polycrystalline compound semiconductors: An overview and review on the voltage-dependent resistance (non-ohmic) feature - Bueno, Paulo R. [UNESP] (2008)
The present review describes mainly the history of SnO2-based voltage-dependent resistors, discusses the main characteristics of these polycrystalline semiconductor systems and includes a direct comparison with traditional ZnO-based voltage-dependent resistor systems to establish the differences and similarities, giving details of the basic physical principles involved with the non-ohmic properties in both polycrystalline systems. As an overview, the text also undertakes the main difficulties involved in processing SnO2- and ZnO-based non-ohmic systems, with an evaluation of the contribution of the dopants to the electronic properties and to the final microstructure and consequently to the system's non-ohmic behavior. However, since there are at least two review texts regarding ZnO-based systems [Levinson, L. M., and Philipp, H. R. Ceramic Bulletin 1985;64:639; Clarke, D. R. Journal of American Ceramic Society 1999;82:485], the main focus of the present text is dedicated to the SnO2-based varistor systems, although the basic physical principles described in the text are universally useful in the context of dense polycrystalline devices. However, the readers must be careful of how the microstructure heterogeneity and grain-boundary chemistry are capable to interfere in the global electrical response for particular systems. New perspectives for applications, commercialization and degradation studies involving SnO2-based polycrystalline non-ohmic systems are also outlined, including recent technological developments. Finally, at the end of this review a brief section is particularly dedicated to the presentation and discussions about others emerging non-ohmic polycrystalline ceramic devices (particularly based on perovskite ceramics) which must be deeply studied in the years to come, specially because some of these systems present combined high dielectric and non-ohmic properties. From both scientific and technological point of view these perovskite systems are quite interesting. © 2007 Elsevier Ltd. All rights reserved.